Impact of virtuality on language teaching and learning. A pedagogical retrospective - Calderón-Delgado, Elena Isabel; Atencio-González, Rously Eedyah; Dávila-Herrería, Patricio Luis; Dávila-Herrería, Juan Carlos (EPISTEME KOINONIA, 2023)
The purpose of this study focused on analyzing the impact of virtuality on language teaching and learning from a retrospective pedagogical point of view. The methodology was based on a quantitative approach under a non-experimental field perspective. A survey was applied to 30 students and 10 teachers belonging to San José La Salle Educational Unit, who made up the study sample. Among the results, the respondents considered virtuality as a positive aspect for the language teaching and learning process, especially in times of pandemic, since it gave rise to an active pedagogical process that prevented the interruption of the training process; in addition, it awakened the motivation of all towards the use of ICTs from a pedagogical approach through the use of social networks and the use of the target language.